A comparative study of the antioxidant, antibacterial, and cytotoxic activities of different varieties of imported ripe Cavendish banana - Mohammad Amzad Hossain; Salem Said Jaroof Al Touby; Faisal Said Hamed Al-abri (International Journal of Secondary Metabolite)
Traditionally, Omanis used bananas to treat gastrointestinal disorders, constipation, and diarrhea. The study aims to determine the pharmacological and toxicological activities of two imported banana varieties collected from the local fruit market. Extracts were prepared separately by soaking the bananas in methanol for seventy-two hours. Then, the extracts were fractionated with various solvents with increasing patterns of polarity to give corresponding crude extracts. All extracts were used to determine their antioxidant, antibacterial, and cytotoxic activities using 2,2-diphenyl-1-picrylhydrazyl (DPPH), agar gel diffusion, and brine shrimp lethality methods. In the Indian ripe bananas, the highest antioxidant activity was obtained from the ethyl acetate and the lowest in water crude extract. However, in the bananas from the Philippines, the highest activity was in chloroform extract and the lowest in water extract. Both extracts displayed moderate antibacterial activity at different concentrations. The range of inhibition was 0-19 mm against Gram-positive and negative bacterial strains. Both banana extracts showed significant cytotoxic activity at all working concentrations. Crude extracts killed all nauplii at the highest concentration of 500 μg/mL. In Indian bananas, the highest cytotoxic activity was found in the water crude extract with an LC50 value of 27.35μg/mL. The lowest was in ethyl acetate and methanol extracts with an LC50 value of 57.54 μg/mL. Almost similar results were obtained from the Philippines. In conclusion, the polar crude extracts prepared from both varieties of ripe bananas have significant pharmacological and toxicological activities. Therefore, polar banana extracts might be agents that can be used as antibiotics.